Phospholipids as inhibitors of amyloid fibril formation - K. O. Vus (Bìofìzičnij Vìsnik, 2016)
Amyloid fibrils are the protein aggregates, whose formation is involved in the pathogenesis of Alzheimer’s disease, systemic amyloidosis, etc. Since there is no effective ways to treat these diseases, developing the new anti-amyloid drugs is of great importance. In this study a series of phospholipids have been tested for their ability to inhibit lysozyme and insulin amyloid fibril formation at acidic or neutral pH and elevated temperature.  The lag time, elongation rate and fibrillization extent were estimated using Thioflavin T fluorescence assay. It is found that the oxidized and charged phospholipids, included into the liposomes, were the most effective inhibitors of the protein fibrillization. By comparing the magnitude and direction of the lipid effect in different lipid-protein systems it was concluded that the reduction of the amyloid fibril formation is governed by hydrophobic and specific liposome-protein interactions. It is hypothesized that the presence of the surface formed by the lipid polar heads is critical for reducing the protein fibrillization extent.